An Augmented Negative Force-Frequency Relationship and Slowed Mechanical Restitution Are Associated With Increased Susceptibility to Drug-Induced Torsade de Pointes Arrhythmias in the Chronic Atrioventricular Block Dog - Sprenkeler, David J.; Bossu, Alexandre; Beekman, Jet D. M.; Schoenmakers, Marieke; Vos, Marc A. (Frontiers in Physiology, 2018)
Introduction: In the chronic AV-block (CAVB) dog model, structural, contractile, and electrical remodeling occur, which predispose the heart to dofetilide-induced Torsade de Pointes (TdP) arrhythmias. Previous studies found a relation between electrical remodeling and inducibility of TdP, while structural remodeling is not a prerequisite for arrhythmogenesis. In this study, we prospectively assessed the relation between in vivo markers of contractile remodeling and TdP inducibility. Methods: In 18 anesthetized dogs, the maximal first derivative of left ventricular pressure (LV dP/dtmax) was assessed at acute AV-block (AAVB) and after 2 weeks of chronic AV-block (CAVB2). Using pacing protocols, three markers of contractile remodeling, i.e., force-frequency relationship (FFR), mechanical restitution (MR), and post-extrasystolic potentiation (PESP) were determined. Infusion of dofetilide (0.025 mg/kg in 5 min) was used to test for TdP inducibility. Results: After infusion of dofetilide, 1/18 dogs and 12/18 were susceptible to TdP-arrhythmias at AAVB and CAVB2, respectively (p = 0.001). The inducible dogs at CAVB2 showed augmented contractility at a CL of 1200 ms (2354 ± 168 mmHg/s in inducible dogs versus 1091 ± 59 mmHg/s in non-inducible dogs, p < 0.001) with a negative FFR, while the non-inducible dogs retained their positive FFR. The time constant (TC) of the MR curve was significantly higher in the inducible dogs (158 ± 7 ms versus 97 ± 8 ms, p < 0.0001). Furthermore, a linear correlation was found between a weighted score of the number and severity of arrhythmias and contractile parameters, i.e., contractility at CL of 1200 ms (r = 0.73, p = 0.002), the slope of the FFR (r = -0.58, p = 0.01) and the TC of MR (r = 0.66, p = 0.003). Thus, more severe arrhythmias were seen in dogs with the most pronounced contractile remodeling. Conclusion: Contractile remodeling is concomitantly observed with susceptibility to dofetilide-induced TdP-arrhythmias. The inducible dogs show augmented contractile remodeling compared to non-inducible dogs, as seen by a negative FFR, higher maximal response of MR and PESP and slowed MR kinetics. These altered contractility parameters could reflect disrupted Ca2+ handling and Ca2+-overload, which predispose the heart to delayed- and early afterdepolarizations that could trigger TdP-arrhythmias.